Analysis of age-related differences in political message framing effects - Morrison, Hayli (Kansas State University, 2016)
This experimental research builds upon the health communications study completed by Rustam Haydarov in 2010, with a similar approach to ascertain how an individual’s age might influence their reaction to political messages. Using a typology of frames by Levin, Schneider and Gaeth (1998), the study utilizes an older demographic (ages 55-70) and a younger comparison group (ages 18-33) to determine a) if both groups find positive advertising messages more favorable than negative advertising messages and b) if the older demographic is more wary than younger counterparts when discussing current events and the future of America. The study used a combination of qualitative and quantitative methods to determine reactions to goal-oriented and loss-oriented message framing in four mock print political campaign advertisements focusing on the topics of healthcare and college education financing. There was greater prevalence of strongly negative and strongly positive reactions among the younger demographic, except in the case of the loss- framed healthcare ad. The older group reacted more strongly to that particular ad, concerning an issue which had great relevance to them. Of the two age groups, the older demographic registered a more even-keeled reaction across the four ads. Overall, this study has focused on how message frame, topic and age of the message receiver combine to affect message resonance in the context of political communications.
Keywords: message effects; political ads; political advertisements; political messages